Gdańskie Targi MHD. (Gdańsk : [s.n.], 1952)
Afisz inf. o targach, które miał miejsce w Sopocie na Molo 29.06-20.07.1952 r.
Keywords: Targi -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Handel -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne